INTERSECTION OF 3-D MARKS WITH INDUSTRIAL DESIGNS: THE CONTEXT OF 3-D SHAPE PROTECTION - Siswoyo, Amelia Anggriany (Universitas Muhammadiyah Ponorogo, 2024)
3-D (three-dimensional) shapes are objects that fall within the scope of regulation of two Intellectual Property Laws, namely the Trademark Law and the Industrial Design Law. There is a regulatory conflict between the Trademark Law and the Industrial Design Law in terms of protecting 3-D (three-dimensional) shapes. This research is normative juridical legal research. This research will use a legal approach and a conceptual approach, as well as data analysis using qualitative descriptive methods. The results of this research conclude that there is a need for determining indicators as a differentiator or boundary line for 3-D (three-dimensional) shapes in terms of protecting Intellectual Property Brands or Industrial Designs. The determining indicators are 'as an identification mark of a trading product', good faith, distinctiveness and The Functionality Doctrine or functionality doctrine.